Determination and Elimination of Microbial Load from Pickle’s Brand in Karachi - Atifa Jamil Kazmi; Naireen Altaf; Sayyada Ghufrana Nadeem (Journal of Basic & Applied Sciences, 2017)
The study is the elementary step to determine the causes of spoilage of fermented products and factors that could be remove to acquire the hygienic fermented products. Pickle is one of the mostly used fermented products especially as a side dish in Eastern countries, but it is developing a high rate of infectious diseases either due to its failing probiotic activity or due to increase harmful microbial flora in the pickle which are dominating the probiotics. The study is based on the determination of microbial load present in the pickle using MPN technique. The growth of fungi such as Aspergillus niger, Aspergillus flavus, Rhizopus, and bacteria Escherichia coli, Lactobacillus acidophilus andBacillus were isolated from the pickles samples used in this study. By using MPN technique, It was observed that the pickle of Rizwan Company had 1100 colonies in 100 ml of sample which can be extremely dangerous for consumption and the pickle from another brand Sundip Company showed the lowest amount i.e. 28 colonies in 100 ml of sample. Other brands that were tested also showed higher amount of organisms in between 150 to 460 colonies in 100 ml of sample. Elimination of the microbial load of pickle also performed on the pickle of National Company that gave a marvelous result the amount of organisms is dropped from 150 colonies to 11 colonies in 100 ml of sample. This study provides preliminary work and open new doors in assessing and improving the quality of pickles available in the market.